Herramienta de monitoreo para la red de la Universidad Nacional de Loja. - Viñán Riofrío, Rolando Antonio (2010)
Of the advance of the connections and protocols of network, one has taken control the creation of tools that allow us to monitor the equipment pertaining to certain network, their characteristics and the traffic necessary that they generate in the network. This because the administrators have a difficult task at the time of wanting to recognize as is the connected equipment and to know if some equipment wants to attempt against the security. This unlmonitoreo system has been developed like a tool Web based on the model client servant using for it free software such as: jsp, jsf, java apache Tomcat and MySQL, which has allowed to obtain a software versatile and easy to maintain. The intention of the system is to optimize the monitoring of equipment pertaining to certain network being allowed us to identify the characteristics of hardware of each equipment and the traffic generated by this.